Delineating Cambodian cities and assessing their sustainable growth with the inclusive wealth index - Thierry Yerema Coulibaly; Shunsuke Managi (Scientific Reports)
Abstract Cambodia is experiencing rapid urbanization, posing significant risks to its natural capital (NC) and long-term sustainability. The absence of robust estimates quantifying the environmental costs of urban expansion has perpetuated this challenge. Here, we present an integrated approach to evaluate the sustainability of urban growth in Cambodia by (1) delineating the boundaries of major cities, (2) assessing urban expansion dynamics, and (3) quantifying the associated depletion of NC from 2010 to 2020. Using Landsat imagery at 30 m resolution and machine learning techniques, we identified clusters of built-up areas to map urban growth. By employing the UN Inclusive Wealth Index framework, we estimate the economic cost of NC depletion, providing insights into the sustainability of urban development. Results reveal that, while urban expansion has maintained positive inclusive wealth growth, NC density has declined by an average of 3% between 2010 and 2020. Projections using a cellular automata model suggest that, if current trends continue, urban expansion could place over USD 56 million worth of ecosystems at risk of depletion by 2030. These findings underscore the need for targeted investments and protective measures to safeguard NC and ensure sustainable urban growth.